Stakeholders’ opinion regarding disabled friendliness of obstetrics and gynaecology services in hospitals of North India - Sharma, Ruchi; Kumar, Ajit; Suri, Vanita; Kaur, Sukhpal; Singh, Amar Jeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hospitals are part of our society. Barriers faced by people with disability (PWD) in hospitals reflect obstacles in society also. Women with disability (WWD) are at particular disadvantage. Our objective was to explore the domain related to the problems that WWD face in accessing obstetrics and gynecology (OBG) services in government institutes/hospitals of Chandigarh. Methods: This mixed quantitative and qualitative research was done during 2013-2017. Stakeholders included WWD, their families, self-help groups, community-based organisations, NGOs, doctors, nurses, public health experts, research scholars and government bodies involved in disability services. Five major government institutes/hospitals of Chandigarh were purposively selected for the study. In-depth interviews were conducted among different groups to gain an insight into their views regarding the degree to which the reproductive health services were disabled-friendly. Results: Most (80-90%) of the stakeholders emphasized the need of making OBG services disabled-friendly. The majority of doctors and nurses said that no special training was given to them to deal with WWD. They opined that SRH needs of WWD were different from other women. Lack of access was the main barrier to OBG care in hospitals reported by 46% of WWD. Most of the hospitals lacked any special provisions for PWD. Conclusions: There is a lack of concern and apathy for WWD in the society. Hospitals lack a disabled-friendly attitude, design and facilities. Access to OBG services for WWD was barrier ridden.